1995
DOI: 10.1111/j.1365-2222.1995.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The lack of effect of benzalkonium chloride on the cilia of the nasal mucosa in patients with perennial allergic rhinitis: a combined functional, light, scanning and transmission electron microscopy study

Abstract: Despite reports of its ciliostatic effects in vitro, BKC did not have such an effect when it was applied for 6 weeks (with/without fluticasone propionate) to the nasal mucosa of perennial allergic rhinitis patients in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 14 publications
0
38
0
1
Order By: Relevance
“…Some investigators have concluded that the inclusion of preservatives, such as BAC, in nasal solutions does not cause any adverse biological effects in vivo [20, 21]. However, these data are inconsistent with the numerous in vitro studies characterizing the adverse effects of preservatives on nasal mucociliary transport and nasal histology [22,23,24].…”
Section: Discussionmentioning
confidence: 71%
“…Some investigators have concluded that the inclusion of preservatives, such as BAC, in nasal solutions does not cause any adverse biological effects in vivo [20, 21]. However, these data are inconsistent with the numerous in vitro studies characterizing the adverse effects of preservatives on nasal mucociliary transport and nasal histology [22,23,24].…”
Section: Discussionmentioning
confidence: 71%
“…Figure 4 and Table 4 show various components and mediators affecting the stimulation or inhibition of nasal mucus secretion. Upon either an extracellular stimuli or an unregulated secretion, the exocytosis of mucin occur, involving the movement of the mucin granule Cigarette smoke Stop/incoordinate 63) Clenbuterol No effect 58) Cocaine Paralize 64) Ephedrine Stimulate 65) Epinephrine Stimulate 66) Fluticasone propionate No effect 67) Guaiphenesin No effect 58) Hyoscine Inhibit 58) Insulin No effect 68,69) Ipratropium No effect 58) Lidocaine No effect 70) Menthol Inhibit 71) Methyl xanthines Stimulate Hypertonic (>1.5% NaCl) Stop 8,54) Hypotonic (<0.45% NaCl) Inhibit 8,54) Microspheres Inhibit 55) pH (>11) Inhibit 54) pH (<6) Inhibit 54) Temperature >40°C Inhibit Temperature <30°C Inhibit Viscosity (increased) Inhibit to the apical surface of the goblet cell. At the surface of the mucosa different components are mixed together and become mucus.…”
Section: Mucinmentioning
confidence: 99%
“…Some studies, including both in vitro and in vivo studies [3,4,5], have suggested that BKC does produce adverse effects on mucociliary activity. Other data, however, suggest BKC lacks deleterious effects [10,11,12,13]. The discrepancy in these results, particularly between in vitro and in vivo findings, could be explained by the possibility of problems in the experimental design and methodology as well as the difference between in vitro and in vivo conditions [13,14].…”
Section: Discussionmentioning
confidence: 60%